Molybdenum trioxide nanopaper as a dual gas sensor for detecting trimethylamine and hydrogen sulfide. Issue 7 (17th January 2017) - Li, Hua-Yao; Huang, Liang; Wang, Xiao-Xue; Lee, Chul-Soon; Yoon, Ji-Wook; Zhou, Jun; Guo, Xin; Lee, Jong-Heun
Abstract : The dual function of a free-standing, flexible, and semi-transparent MoO3 nanopaper sensor to detect TMA and H2 S in a highly selective manner. Abstract : A free-standing, flexible, and semi-transparent MoO3 nanopaper was fabricated using ultralong MoO3 nanobelts (length ∼ 200 μm; width 200–400 nm), and its gas-sensing characteristics were investigated. The sensor exhibited high responses (resistance ratio) of 49 to 5 parts per million (ppm) hydrogen sulfide (H2 S) at 250 °C and 121 to 5 ppm trimethylamine (TMA) at 325 °C with excellent gas selectivity, demonstrating its dual function for gas detection. Moreover, the sensor showed promising potential for the all-in-one detection of three representative offensive odors (TMA, H2 S, and NH3 ) simply by tuning of the sensing temperature. This particular performance is attributed to the high chemical affinity of MoO3 to H2 S and the acid–base interaction between basic TMA/NH3 and acidic MoO3 . The mechanism underlying the control of gas selectivity by modulating the sensor temperature was investigated by Diffuse Reflectance Infrared Fourier Transform (DRIFT) measurements.